Comparative evaluation of the marginal fit of inlays fabricated by conventional and digital impression techniques: A stereomicroscopic study - Anamika Sharma; Dax Abraham; Alpa Gupita; Arundeep Singh; Naresh Sharma (Wolters Kluwer Medknow Publications, 2020)
Context: Marginal fit being the prime concern of indirect restorations. Inlays can be either fabricated by conventional technique or computer-aided design and computer-aided manufacturing (CAD/CAM) techniques. CAD/CAM is the most evolving digital technique with faster, quicker, and precise results. Aims: The aim of this study is to evaluate and compare the marginal fit of MOD inlays fabricated with two different CAD/CAM methods and conventional fabrication methods. Settings and Design: Mesio-occlusal-distal preparation was done on a maxillary premolar typhodont tooth and divided into the following groups. Group A: 30 inlays were fabricated through the conventional impression technique. Group B: Preparation was scanning using an intraoral scanner followed by subtractive milling (Group B1) and subtractive milling of wax patterns (Group B2). Similarly, subgrouping was carried out for Group C except that an extraoral scanner was used. Occlusal and the cervical marginal fit were assessed using the replica technique and stereomicroscope. One-way ANOVA followed by Tukey honestly significant difference post hoc test for determining differences at a 95% level of confidence (P = 0.05). Results: Group A had the highest marginal discrepancy in comparison to Group B and Group C at occlusal and cervical edges, whereas subtractive milling showed comparatively better results than subtractive milling of wax patterns at cervical edges and similar results at occlusal edges. Conclusions: Ceramic inlays fabricated by subtractive milling yielded better results.